Characterisation of commercial Perna canaliculus samples and development of extemporaneous oral veterinary paste formulations containing Perna. Issue 18 (16th September 2016) - Juliano, Claudia; Manconi, Paola; Cossu, Massimo
Abstract: Perna canaliculus is a nutritional supplement recently studied and highly recommended for its anti-inflammatory effects in both animals and humans. In this study, the physicochemical properties, the microbiological quality, the total lipid content and fatty acids composition of three commercial samples of Perna powder were determined. Subsequently, three simple formulations of extemporaneous oral pastes containing Perna were prepared and designed for veterinary use. Their microbiological stability was assessed after 1-month storage at either room temperature or 35 °C. The results demonstrated that commercial Perna samples lack homogeneity, in regard to some technological properties and fatty acid composition; therefore, a preliminary characterisation of commercial Perna samples is recommended to assure the quality of formulations containing this nutritional supplement. Oral paste formulations are easy and simple to prepare and show good physical and microbiological stability, suggesting their large-scale production. Graphical abstract: